Development Guidelines for School Administrator’s Roles in The King’s Phumibol Science to The Philosophy of Sufficiency Economy in Office of Institute of Vocational Education Northern Region - Umnuayrat, Sopa Umnuayrat (Journal of Inclusive and Innovative Education, 2020)
The purposes of this research were to: 1) To study the roles of administrators in the King’s Phumibol science to the philosophy of sufficiency economy in office, the sample group was 439 administrator and teacher, the instruments were questionnaire. 2) To development guidelines administrators’ roles, the key informant was 5 specialists, the instruments were semi-structured interview. 3) To creation the development guidelines administrators’ roles, the researcher analysis result in phase 1, phase 2 and creation the development guidelines. 4) To evaluation the development guidelines administrators’ roles, the key informant was 15 specialists, the instruments were assessment form. Data analyses form questionnaire and assessment form were mean and standard deviation. The research findings showed that: 1) The overall of the roles of administrators in the King’s Phumibol science to the philosophy of sufficiency economy in office was at a high level. Considering each aspect orders of academic administration was at a highest level, followed by general administration management, human resource management and budget management. 2) The result of creation the development guidelines administrators’ roles is appropriate with 4 sides and 32 guidelines. 3) The result of evaluation the development guidelines administrators’ roles has high level suitability, feasibility and utility.